Hippo/Mst1 stimulates transcription of the proapoptotic mediator NOXA in a FoxO1-dependent manner - Vališ, Karel; Procházka, Lubomír; Bouřa, Evžen; Chladova, Jaromira; Obšil, Tomáš; Rohlena, Jakub; Truksa, Jaroslav; Dong, Lan-Feng; Ralph, Stephen J; Neužil, Jiří (Cancer research, 2011)
The proapoptotic protein Noxa, a member of the BH3-only Bcl-2 protein family, can effectively induce apoptosis in cancer cells, although the relevant regulatory pathways have been obscure. Previous studies of the cytotoxic effects of α-tocopheryl succinate (α-TOS) on cancer cells identified a mechanism whereby α-TOS caused apoptosis requiring the Noxa-Bak axis. In the present study, ab initio analysis revealed a conserved FoxO-binding site (DBE; DAF-16 binding element) in the NOXA promoter, and specific affinity of FoxO proteins to this DBE was confirmed by fluorescence anisotropy. FoxO1 and FoxO3a proteins accumulated in the nucleus of α-TOS-treated cells, and the drug-induced specific FoxO1 association with the NOXA promoter and its activation were validated by chromatin immunoprecipitation. Using siRNA knockdown, a specific role for the FoxO1 protein in activating NOXA transcription in cancer cells was identified. Furthermore, the proapoptotic kinase Hippo/Mst1 was found to be strongly activated by α-TOS, and inhibiting Hippo/Mst1 by specific siRNA prevented phosphorylation of FoxO1 and its nuclear translocation, thereby reducing levels of NOXA transcription and apoptosis in cancer cells exposed to α-TOS. Thus, we have demonstrated that anticancer drugs, exemplified by α-TOS, induce apoptosis by a mechanism involving the Hippo/Mst1-FoxO1-Noxa pathway. We propose that activation of this pathway provides a new paradigm for developing targeted cancer treatments.
Keywords: signální transdukce; lymfom T-buněčný; Humans; nádorové buněčné linie; Forkhead Transcription Factors; malá interferující RNA; promotorové oblasti (genetika); Proto-Oncogene Proteins c-bcl-2; lidé; Carcinoma, Non-Small-Cell Lung; protein-serin-threoninkinasy; Lung Neoplasms; Promoter Regions, Genetic; nádory plic; Signal Transduction; RNA, Small Interfering; polymerázová řetězová reakce s reverzní transkripcí; Apoptosis; protoonkogenní proteiny c-bcl-2; apoptóza; alfa-tokoferol; Jurkat buňky; Protein Serine-Threonine Kinases; Lymphoma, T-Cell; alpha-Tocopherol; Transcription, Genetic; genetická transkripce; Jurkat Cells; forkhead transkripční faktory; Cell Line, Tumor; Reverse Transcriptase Polymerase Chain Reaction; nemalobuněčný karcinom plic